Attitude and its associated factors towards the nursing profession among BSc nursing students learning at governmental universities in Amhara region, northwest Ethiopia, 2021 - Sahileslassie Afewerk; Eleni Tesfaye; Asemarie Kebede; Destaw Endeshaw (Elsevier, 2023)
Background: Nursing is a noble profession that requires nurses to devote their entire lives to provide comprehensive care to those who are suffering. Nursing has faced numerous cultural challenges, including negative attitude that may hinders people from entering the field, and not performing their responsibilities as expected. This isn't a problem for a single country; it's a worldwide concern. In Ethiopia, no published research on nursing students' attitude. This study aimed to assess the attitude and to determine its associated factors towards the nursing profession among Bachelor of Science nursing students in Amhara region, northwest Ethiopia. Methods: An institution-based cross-sectional study was conducted from April 1 to 15, 2021. Simple random sampling technique was used to select 423 participants. Data were collected by using a structured self-administered questionnaire, entered into Epi-data version 4.6, and exported to SPSS version 23.0 for analysis. Descriptive and inferential statistics were used to present findings. Binary logistic regression was employed to identify associated factors. Result: Among 413 respondents, 66.8% had a positive attitude towards the nursing profession. The result showed that being female [AOR = 2.150, (95% CI: 1.341-3.449)], admitted in the generic program [AOR = 3.241, (95% CI: 2.038-5.154)], and reason for choosing the nursing school by the desire to help others [AOR = 3.066, 95% CI (1.838-5.113)] were significantly associated with nursing students' attitude towards their profession. Conclusion: This study found that the study participants had relatively low positive attitude towards the nursing profession. Universities should work to improve the nursing students' attitude towards their profession.